Criticism, Critique, and Crisis in Assessing the Work of René Girard - Goodhart, Sandor ca. 20./21. Jh. (Bulletin for the study of religion, 2016)
Perhaps it is time to begin the second stage of René Girard's passing: the labor of a full critical assessment of his life's work. In preparation, I thought I might consider some of the misunderstandings to which his work has been subject. After briefly recalling Girard's three big ideas (mimetic desire, sacrificial violence and the scapegoat mechanism, scriptural revelation of the founding murder), I will suggest the most common misapprehensions: (1) the idea of the innocent victim; (2) the idea that there is a good and a bad mimesis; and (3) the relation between Girardianism and the ethical. Other issues remain to be clarified. Among them are the following ideas: (1) that Girardian thinking is scientific; (2) that it is not an advocacy of any kind but a way of producing knowledge; (3) that the center of gravity remains the process of sacrificial genesis and the scapegoat mechanism, mimetic desire, and their scriptural revelation serve that end; (4) that violence is not a thing or essence but difference gone wrong; and finally (5) that Girardian thinking is not an essentialism; it is not about what is really good, true, beautiful, or present but strategies of doing and acting. We best honor the work of our teachers and foremost thinkers by endeavoring to get it right for future generations for whom we, who have known the individual personally, remain a conduit.